A simple colorimetric chemosensor for relay detection of Cu2+ and S2− in aqueous solution. Issue 2 (17th January 2018) - Kim, Min Seon; Jung, Jae Min; Ahn, Hye Mi; Kim, Cheal
Abstract: A simple colorimetric chemosensor1 was developed for the sequential detection of Cu 2+ and S 2− . Sensor1 could rapidly detect Cu 2+ by an obvious color change from colorless to yellow. The binding mode of1 to Cu 2+ was determined to be a 1:1 complexation stoichiometry through Job plot and ESI-mass spectrometry analyses. The sensing mechanism of Cu 2+ by1 was proposed by theoretical calculations. Importantly, the detection limit for Cu 2+ was found to be 0.12 μM, which was much lower than the recommended value (31.5 μM) of the World Health Organization (WHO). Additionally, 1 could detect and quantify Cu 2+ in real water samples. Moreover, the resulting1 -Cu 2+ complex could be used as a highly selective colorimetric sensor for S 2− in the presence of various anions without any interference. The detection limit for S 2− was determined to be 1.66 μM, which was much lower than the guideline (14.8 μM) recommended by WHO in fresh water. Abstract :